Review of methods for the high-cycle fatigue strength assessment of steel structures subjected to sub-zero temperature - Braun, Moritz; Ehlers, Sören (Marine Structures, 2022)
In recent years, there has been a growing interest in exploring the resources of the Arctic regions and an increase in shipping in regions with seasonal sub-zero temperatures. Such low temperatures impose challenging requirements for the structural integrity of steel structures and their weldments. Hence, specific knowledge of the behavior of materials and weldments and how to account for temperature effects is crucial to ensure safe operations. A number of recent studies have shown that fatigue strength at sub-zero temperatures is a major knowledge gap. This is exacerbated by the fact that this effect is not addressed in international standards. In this context, this study presents a comprehensive review of the current state of the art of high-cycle fatigue strength assessment methods for steel structures subjected to sub-zero temperature. The main objective is to provide an overview of how to account for temperature effects on fatigue strength when designing steel structures.